2009
DOI: 10.1007/s00595-008-3859-7
|View full text |Cite
|
Sign up to set email alerts
|

Sacral hemangiopericytoma involving the retrorectal space: Report of a case

Abstract: A primary hemangiopericytoma (HP) of the bone is rare, because the vast majority of these tumors arise in soft tissue. This report presents a case of a hemangiopericytoma in the sacrum (S1-S2) with extension to the retrorectal space. Only a few cases of osseous hemangiopericytomas in the sacrum and involving the retrorectal space have so far been reported. The difficult diagnosis of HP and the surgical strategy was chosen according to the location of the lesion in the sacrum and retrorectal space. A local exci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
0
9
0
1
Order By: Relevance
“…Approximately 80 cases of MPE have been reported in the English literature, and we analyzed the clinical characteristics of 57 cases [3,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33] based on information and articles we found in MEDLINE (table 1). The mean age of MPE patients was 59 years, with similar gender distribution, and the left pleural cavity was more commonly involved.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 80 cases of MPE have been reported in the English literature, and we analyzed the clinical characteristics of 57 cases [3,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33] based on information and articles we found in MEDLINE (table 1). The mean age of MPE patients was 59 years, with similar gender distribution, and the left pleural cavity was more commonly involved.…”
Section: Discussionmentioning
confidence: 99%
“…It is derived from the pericytes of Zimmerman, which are pericapillary mesenchymal cells with a contractile ability [3, 4]. Owning to its vascular origin, HP can arise in any part of the body; however, the vast majority of these tumors occur in the soft tissue [4, 5, 6]. HP of the bone is very rare, accounting for 0.1% of malignant primary bone tumors and 11% of malignant vascular bone tumors [5, 6].…”
Section: Discussionmentioning
confidence: 99%
“…Due to its vascular origin, HP can arise in any part of the body, with the vast majority occurring in the soft tissue [4, 5, 6]. However, primary HP of the bone is very rare [5, 6]. We present a case of AI as a paraneoplastic skin manifestation of a primary, osseous HP, accompanied by multiple liver metastases, an association that, to our knowledge, has not been previously reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HPCs in the spine may involve the structures of the vertebra and the spinal canal, including the extradural and intradural space. Our search of the literature showed that 140 cases of HPC in the spine had been reported (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(49)(50)(51)(52)(53)(54)(55)(56), and 64 cases were extradural (2, 4-6, 8-10, 15, 20-22, 24, 25, 27, 28, 31, 32, 34, 35, 37, 40-42, 44-46, 49, 51, 53-55) (Table I). Here we present a case of primary HPC invasion in the cervicothoracic spine, as well as presenting a review of the literature.…”
Section: Introductionmentioning
confidence: 99%